Marketing financial services - Farquhar, Jillian (Palgrave Macmillan, 2010)
"This revised edition of one of the classic texts in the area is timely and topical; key elements of marketing as they apply to financial services are clearly articulated and supported with practical illustrations. Building on extensive accumulated experience of the sector, Meidan and Dawes Farquhar provide students with a thoughtful and insightful treatment of the many challenges associated with fair and effective marketing for retail financial services.'- Professor Christine Ennew, Pro-Vice-Chancellor and Professor of Marketing, University of Nottingham, UK" "A valuable resource for students and practitioners of financial services marketing, packed with up-to-date trends and useful examples that bring this fascinating area of study to life.'- Dr Tina Harrison, Senior Lecturer in Financial Services Marketing, University of Edinburgh, UK, and Editor-in-Chief of the Journal of Financial Services Marketing" "Marketing Financial Services recognizes that the main function of the financial services marketer is decision-making. It focuses on the major types of decisions - and problems - facing marketing executives. Strategies to win and retain B2B and B2C customers are discussed in the context of many financial services sectors, including banks, insurance companies, investment trusts and stock exchanges." "This second edition has been thoroughly updated to reflect changes in the industry and the availability of new technologies. The text has been made more accessible and includes gripping case studies to demonstrate the realities of financial services marketing in an unstable and competitive environment." "Marketing Financial Services is essential for undergraduates and postgraduates studying modules in Services Marketing and Financial Services Marketing. It is also recommended reading for students researching financial services for higher degrees."--BOOK JACKET.